SELF-ACTUALIZATION AND EXPERIENTIAL LEARNING THEORIES: IMPLICATIONS FOR VOCATIONAL TRAINING AND COUNSELLING (Journal of Guidance and Counselling Studies, 2021)
This paper examines the relevance of Abraham Maslow’s self-actualization (motivational) theory and Kolb’s experiential learning theory for the pre-service (vocational) training of the individual by the training institution to acquire the requisite knowledge and skills for the workplace. Each employable personnel should have the appropriate subject matter knowledge and the associated critical and analytical skills applicable to the practical context of work. He has to learn from experience and take responsibility for improving own performance on the job. Maslow’s model provides for constant striving by the individual to do things to the best of one’s ability, and better than before, towards self- actualization. This would likely motivate the individual towards acquiring the needed training for the vocation or career aspired to. Kolb’s experiential learning model emphasizes the value/role of concrete experience by doing in both training and re-training for skills acquisition of the individual by the training institution for all levels of employment. To improve individual personnel’s knowledge and skill for direct work applications and ultimately improve organisational performance, the training institution has to knit together the self-actualization need of the individual and the requisite training as propellant for career choice or placement. The implications of these theories for pre-ser\’ice training, workplace training and counselling have been highlighted and recommendations made for improved overall instructional training environment and vocational counselling.